Sensory System Responses to Human-Induced Environmental Change - Kelley, Jennifer L.; Chapuis, Lucille; Davies, Wayne I. L.; Collin, Shaun P. (Frontiers in Ecology and Evolution, 2018)
Sensory input to the central nervous system is the primary means by which animals respond to variation in their physical and biological environments. It is well established that key threats such as habitat destruction, the introduction of non-native species, and climate change are imposing significant pressures on natural ecosystems, yet surprisingly few studies have examined how these threats impact the senses or determine species’ responses to environmental change. This review focuses on how anthropogenic impacts on aquatic ecosystems can have a detrimental effect on the sensory systems of aquatic organisms and how these modalities can act to influence genetic and non-genetic (e.g. developmental) responses to environmental change, which in turn can cause knock-on effects in a range of other biological systems. Species often exhibit unique sensory specializations that are suited to their behavioral requirements; at present it is unclear whether and how sensory systems have the capacity to respond to environmental change through genetic adaptation and/or sensory plasticity, and on what timescale this might occur. Sensory systems lie at the forefront of how various species respond to environmental perturbation. As such, determining the important role they play in determining fitness is critical for understanding the effects of external processes such as habitat degradation and climate change. Given the current consensus that human impacts and environmental changes are potentially highly detrimental to the delicate balance of the biome, knowing how organisms respond, and to what degree adaptation is physiologically and behaviorally limited, warrants urgent attention.